The market potential for increased small ruminant production in southwest Nigeria - Okali, C.; Upton, M. (International Livestock Centre for Africa, 1984)
Discusses the market potential for increased sheep & goat production in southwest Nigeria based on an analysis of supply & demand and prices of goats & sheep in both rural & urban markets.